Can compression stockings reduce the degree of soccer match-induced fatigue in females?. Issue 3 (3rd July 2019) - Pavin, Larissa Neves; Leicht, Anthony S.; Gimenes, Samuel Valencia; da Silva, Bruno Victor Corrêa; Simim, Mário Antônio de Moura; Marocolo, Moacir; da Mota, Gustavo Ribeiro
ABSTRACT: Soccer-induced fatigue and performance are different between the sexes. The effect of compression stockings (CS) use on fatigue during the soccer match in females is unknown. Thus, we evaluated the impact of CS use during a female soccer match on match-induced fatigue. Twenty soccer players were randomly allocated to two groups ( n  = 10 for each group): CS and Control (regular socks), and equally distributed within two teams. At rest (baseline 48-h before the match) and immediately post-match, we assessed agility T-test, standing heel-rise test and YoYo Intermittent Endurance Test level 2 (YoYoIE2) performance. Effort during the match (heart rate and rating of perceived exertion) was similar ( p  > 0.05) between groups. The YoYoIE2 performance was decreased post-match ( p  < 0.05) equally for both groups. Otherwise, the CS group exhibited a greater post-match performance ( p  < 0.05) for the agility T-test and heel-rise test (large effect sizes). Therefore, we conclude that the use of CS during an amateur female soccer match resulted in less match-induced fatigue.